2014
DOI: 10.1093/jat/bku009
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Identification of 117 Pesticides Commonly Involved in the Poisoning of Wildlife Using GC-MS-MS and LC-MS-MS

Abstract: Poisoning with agricultural chemicals is a major threat for wildlife all over the world. We have developed and validated an analytical scheme aimed to the identification and quantification of a wide range of pesticides in fresh liver from wildlife specimens that are routinely delivered to the forensic laboratories for toxicological investigation. The proposed method is comprised of a general solid-liquid extraction followed by purification steps and three complementary liquid or gas chromatographic analyses wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 20 publications
0
34
0
1
Order By: Relevance
“…In past years, pesticide residues in food were detected by different chromatographic methods . Although chromatographic methods possess the key advantages of accuracy and sensitivity, their disadvantages include high cost, difficulty of use, complex and higher‐quantity sample pretreatment, inability to perform online analysis, and the use of large amounts of organic solvents .…”
Section: Introductionmentioning
confidence: 99%
“…In past years, pesticide residues in food were detected by different chromatographic methods . Although chromatographic methods possess the key advantages of accuracy and sensitivity, their disadvantages include high cost, difficulty of use, complex and higher‐quantity sample pretreatment, inability to perform online analysis, and the use of large amounts of organic solvents .…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of an incident that involves the death of wildlife specimens generally consists of a field inquiry, a postmortem examination and when necessary, chemical analysis to determine whether a poison might be responsible (5). For pesticide detection, multistage mass spectrometry (MS/MS) is considered a very useful tool to detect low levels of an analyte when coupled with chromatographic techniques (22). For our toxicological analysis, we used a triple quadrupole mass spectrometry analyzer, operated in the selective reaction monitoring mode which improved significantly both the sensitivity and selectivity of the analytical determination, as the Luzardo et al In our study, the pathological exam revealed predominant pulmonary lesions.…”
Section: Resultsmentioning
confidence: 99%
“…As a similarity the use of sonication should be mentioned, which improves the extraction efficiency and improve the recoveries of certain key pesticides, such as carbofuran. Therefore Luzardo et al(22) added a 5-min sonication to the extraction protocol, which in our cases lasted 15-min. Another method using homogenized 2 g liver samples is based on a new analytical multiclass method named QuEChERS technique(35), developed by Sell et al and validated according to the requirements of SANCO/12571/2013(34).…”
mentioning
confidence: 99%
“…The modern field of forensic sciences dates back to the 1800s and includes analysis of latent fingerprints, questioned documents, hair morphology, serology, and ballistics. Some wildlife forensic applications use these same classic techniques: fingerprints lifted from traps, feathers, eggs, or elephant tusks , microscopic examination of bullets retrieved from a carcass , or toxicological analysis of remains for the presence of poisons . Though the evidence items and the species involved differ between wildlife and human forensic laboratories, the point of many of these classic analyses is the same—to determine who was involved and how and where the crime occurred.…”
Section: Similarities and Differences Between The Common Questions Inmentioning
confidence: 99%